Dominasi ragam akulturasi lokal-moderen pada bangunan Casablancka residence, Bali - Efraim Desprinto Lalu; Bachtiar Fauzy (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Domination of local-modern acculturation in Casablancka residence, Bali The phenomenon of local-modern architecture acculturation is important to explore because it can be used as a concept of contemporary architecture (kiwari architecture). The research object in this study is Casablancka Residence building in Bali. The object of research is a new building which is still rarely studied, especially from the aspect of architectural acculturation. This research aims to uncover various forms of acculturation of local and modern architecture in terms of various aspects of the form of acculturation, also to see which one is more dominant between local and modern architecture in the Casablancka Residence building. The Archetype Theory is then used to uncover the architectural phenomenon of Casablancka Residence building. Through a descriptive-analytical-interpretative approach, the characteristic of the acculturation will be revealed. The results of this study found a stronger dominance of local elements whose outlines appear on the roofs and floors of buildings that use strong local forms and materials, while modern elements are more dominant on the walls of buildings dominated by modern glass materials. The benefits of this study are expected to contribute positively for the community to raise the awareness of the importance of locality in building and preserving local culture and architecture. The other benefits are to increase architectural knowledge for academics and practitioners.